Authenticity and traceability in beverages. (30th March 2019) - Kamiloglu, Senem
Highlights: Adulteration originates non-authentic beverages, which may possess health risks. Geographical origin is one of the major authenticity issues for beverages. Fruit juices, coffee, tea and alcoholic beverages are likely to be target of fraud. Chemical, biomolecular and isotopic methods are applied to determine authenticity. Abstract: Nowadays, consumers expect to be sure that a food product complies with its label and demand further information regarding the geographical origin of the product. Beverages are among the most likely foods to be the target of food fraud. Adulteration through practices including, among the others, mixing or substituting the original material with other materials or useless parts of the same materials, which do not conform to the official standards and the food label, originate non-authentic beverages. For the determination of beverage authenticity, chemical, biomolecular and isotopic approaches could be applied depending on the level in the structure of the matter for obtaining the target information. This review highlights the recent key studies and related analytical approaches on authentication of beverages including fruit juices, coffee and tea, and wine and other alcoholic beverages.